IMPACT OF AGRICULTURAL LOAN ON DRY SEASON FARMING IN MUBI METROPOLIS ADAMAWA STATE - Yahaya, Adamu (International Journal of Research -GRANTHAALAYAH, 2018)
Until recently, farming was predominantly a seasonal business in Nigeria where most cropping are observed during the raining season. Increase in demand for food couple with the recent government policy of diversification motivate people into dry season farming. Therefore, this paper investigates the impact of agricultural loan on dry season farming in Mubi metropolis. The methodology adopted was purely descriptive and data used were primarily sourced via questionnaire and interviews. Two sets of the dry season farmers were identified as: grain and vegetable farmers in the study area. A total of fifty (150) farmers were randomly selected within the metropolitan space of Mubi north and south local government areas. The Data collected was analyzed using descriptive statistics through frequency tables and percentages. It is evident from the analysis that 83% of the respondents were male and most of them were in their active ages: 18 to 59 years (93%). The study further revealed that 97% of the farmers’ farm sizes were below 0.76ha and 57% of which are inherited by the farmers while only 10% of the farmers enjoy government loan as 90% finance their farming by personal savings and other sources. Moreover, 40% of the farmers get assistance from politicians in form of farming tools. It is therefore concluded that most dry season farmers in Mubi metropolis do not enjoy agricultural loan from government even though the few that benefited from it testified for remarkable yield increase. The study recommends that government should come to the aid of dry season farmers by providing drainage generators, canals (tube), fertilizers, chemicals, loan and other assistance for more yield from the dry season farming in Mubi metropolis.